Attenuation of Paraquat-Induced Nephrotoxicity and Dysfunction in Male Wistar Albino Rats - Ujowundu, Cosmas O.; Anaba, Peter-Oscar I.; Ulinasombu, Ngozi B.; Ujowundu, Favour N.; Igwe, Kalu O.; Ogbuagu, Henry D. (Innovative Biosystems and Bioengineering, 2020)
Background. Paraquat (PQ) is a pesticide commonly used in the control of weed in agricultural practices worldwide. Exposure to PQ has adverse biochemical and physiological consequences to humans and animals. The mechanism of toxicity is linked to the generation of reactive oxygen species and subsequent lipid peroxidation. Presently, no single effective antidote to PQ toxicity has been established. Therefore, the need to continually investigate different treatment approaches is of paramount importance. Objective. This study evaluated the capacity of selected dietary supplements to attenuate paraquat-induced kidney dysfunction and damages by determining some kidney function biomarkers and oxidative parameters. Methods. Thirty-six Wistar albino rats were randomly separated into six groups. Each group (except Normal control) was intoxicated every other day with 1.5 mg/kg body weight of PQ and four groups (except PQ and Normal control groups) were treated daily with 40 mg/kg of garlic, glutathione and vitamin C for two weeks. Results. The results showed significant (p < 0.05) increases in concentration of kidney malondialdehyde, urea, creatinine, and blood lipid profiles. Also, significant decrease in concentrations of high-density lipoprotein cholesterol, kidney glutathione and total antioxidant capacity were presented by PQ control group compared to other PQ exposed groups treated with the antioxidant compounds. Conclusions. PQ-induced changes indicated kidney dysfunction and damage. However, the administration of antioxidant supplements attenuated the PQ-induced biochemical and physiological dysfunction in the rats.